Introduction to transportation engineering - Banks, James H. (McGraw-Hill, 2004)
Provides an introduction to intermodal transportation. This book strives to provide a background in transportation planning, analysis, and design while emphasizing the social, economic, and political context of transportation engineering. It places major emphasis on important practical topics.